Outer Membrane Permeabilization Is an Essential Step in the Killing of Gram-Negative Bacteria by the Lectin RegIIIβ - Miki, Tsuyoshi (Public Library of Science, 2013)
The C-type lectin RegIIIβ can kill certain Gram-positive and Gram-negative bacteria. The susceptibility of S. Typhimurium depends on the bacterial growth phase, i.e., bacteria from the logarithmic growth phase do bind RegIIIβ and are subsequently killed. Lipid A is one of the bacterial targets for RegIIIβ. However, at the molecular level, it is not understood how RegIIIβ interacts with and kills Gram-negative bacteria. Here, we show that RegIIIβ interacts with Gram-negative bacteria in two distinct steps. Initially, it binds to surface-exposed lipid A. The lipid A can be shielded by the O-antigen of lipopolysaccharide (LPS), as indicated by the exquisite susceptibility of wbaP mutants to RegIIIβ-mediated killing. Increased cell viability after incubation with an anti-lipid A antibody also supports this conclusion. This RegIIIβ-binding permeabilizes the outer membrane to hydrophobic dyes like Ethidium bromide or to bulky bacteriolytic enzymes like lysozyme. Conversely, compromising the outer membrane integrity by the mild detergent Triton X-100 enhances the antibacterial effect of RegIIIβ. Based on our observations, we conclude that RegIIIβ interacts with Gram-negative bacteria in two subsequent steps. Initially, it binds to the outer membrane thus leading to outer membrane permeabilization. This initial step is necessary for RegIIIβ to reach a second, still not well understood target site (presumably localized in the periplasm or the cytoplasmic membrane), thereby triggering bacterial death. This provides novel insights into the outer membrane-step of the bactericidal mechanism of RegIIIβ.